2008
DOI: 10.1002/cphc.200800320
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativity between the Dihydrogen Bond and the N⋅⋅⋅HC Hydrogen Bond in LiH–(HCN)nComplexes

Abstract: The cooperativity between the dihydrogen bond and the NHC hydrogen bond in LiH-(HCN)(n) (n=2 and 3) complexes is investigated at the MP2 level of theory. The bond lengths, dipole moments, and energies are analyzed. It is demonstrated that synergetic effects are present in the complexes. The cooperativity contribution of the dihydrogen bond is smaller than that of the NHC hydrogen bond. The three-body energy in systems involving different types of hydrogen bonds is larger than that in the same hydrogen-bonded s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…The negative E coop indicates a synergetic effect between both interactions. The E coop in the trimer is larger than that in LiHÀHCNÀHCN complex [31] but smaller than that in dimethyl dulfoxideÀH 2 OÀH 2 O complex. [33] This cooperative energy is so large that it is greater than the binding energy in water dimer.…”
Section: Cooperativity Between Lithium Bond and Hydrogenmentioning
confidence: 84%
See 1 more Smart Citation
“…The negative E coop indicates a synergetic effect between both interactions. The E coop in the trimer is larger than that in LiHÀHCNÀHCN complex [31] but smaller than that in dimethyl dulfoxideÀH 2 OÀH 2 O complex. [33] This cooperative energy is so large that it is greater than the binding energy in water dimer.…”
Section: Cooperativity Between Lithium Bond and Hydrogenmentioning
confidence: 84%
“…[28][29][30] Recently, the cooperativity between the different types of hydrogen bonds has been paid much attention. [31][32][33] The results show that a large synergetic effect is present in these systems. However, the study of the cooperativity of lithium bond is rare.…”
Section: Introductionmentioning
confidence: 90%
“…In particular, great emphasis has been placed on the interplay between multiple hydrogen bonds [66][67][68][69][70][71][72][73][74][75][76][77], hydrogen and dihydrogen bonds [78][79][80] and, most recently, hydrogen and halogen bonds [34,[81][82][83][84][85][86][87][88][89][90][91]. Parra et al investigated the cooperative effects of bifurcated hydrogen bonding.…”
Section: Interplay Between Non-covalent Interactionsmentioning
confidence: 98%
“…[34] It has been demonstrated that it is present not only in the same type of interaction, but in different types of interactions as well. [35][36][37][38][39][40][41] One prominent effect of cooperativity is the enhancement of interaction strength. Thus, we want to enhance halogen-hydride halogen bonding by combining it with another interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we want to enhance halogen-hydride halogen bonding by combining it with another interaction. Considering that a weaker interaction can be enhanced by another stronger one, [35][36][37][38][39] we designed the We designed M 1 ···C 6 H 5 X···HM 2 (M 1 = Li + , Na + ; X= Cl, Br; M 2 = Li, Na, BeH, MgH) complexes to enhance halogen-hydride halogen bonding with a cation-p interaction. The interaction strength has been estimated mainly in terms of the binding distance and the interaction energy.…”
Section: Introductionmentioning
confidence: 99%